Introduction to Special Issue: Moving Through Trails and Trials Toward Community Wellness - McCaffrey, Shanne (International Journal of Child, Youth and Family Studies, 2020)
The Child and Youth Care in Action VI Conference — Moving Through Trails and Trials Toward Community Wellness took place April 25–27, 2019 at the University of Victoria in Victoria, British Columbia. Working from the position of trying to inhabit the space of a good relative, all conference preparations and work, all details, protocols, and calls to community were guided by the desire to achieve optimal and positive outcomes. From this location we are very grateful to provide this special conference edition of the International Journal of Child, Youth and Families Studies.